Patient Experiences in Selecting a Medicare Part D Prescription Drug Plan - Stults, Cheryl D (J Patient Exp, 2017)
INTRODUCTION: Medicare beneficiaries often report that the process of choosing a prescription drug plan is frustrating and confusing and many do not enroll in the plan that covers their drugs at the lowest cost. METHODS: We conducted 4 focus groups to understand beneficiaries’ experiences in selecting a drug plan to identify what resources and factors were most important to them. Participants were patients served by a multispecialty delivery system and were primarily affluent and Caucasian. RESULTS: While low cost was essential to many, other characteristics like having the same plan as a partner, company reputation, convenience, and anticipation of possible future health problems were sometimes more important. Although some used resources including insurance brokers, counselors, and websites beyond Medicare.gov, many expressed a desire for greater assistance with and greater simplicity in the choice process. CONCLUSION: Although older adults would likely benefit from greater assistance in choosing Medicare Part D prescription drug plans, more research is necessary to understand how to help with decision-making in this context.